Annular Squared Tapered EBG Microstrip Bandstop Filter with Improved Performance - Gupta, Isha (My University, 2015)
Filtering of undesired frequencies can be done by using shunt stubs and stepped impedance lines. These techniques are typically narrow band and require large circuit area. In order to solve the problem of conventional filters, one possible way to reject a band of frequencies is to use Electromagnetic Bandgap (EBG) Structure. Periodic structures that allow circulation of electromagnetic waves in a specific frequency band for certain angles of incidence and polarization senses are known as electromagnetic band- gap (EBG) structures. The peculiar feature of the 2-D EBG structures is due to the presence of the stopband where electromagnetic waves are prohibited to propagate. In this thesis a Low Pass Filter is designed with squared EBG etched in the ground plane. It is concluded that by employing the squared uniform EBG instead of circular EBG in the ground plane the bandwidth is improved. By employing other tapering technique on the square EBG other filter characteristics such ripple level in the passband and attenuation of the stopband are also improved. Secondly this thesis presents squared Chebyshev (SC-EBG) tapered and squared annular Chebyshev and Kaiser (SACK-EBG) tapered compact electromagnetic bandgap microstrip bandstop filter. The compact EBG provides a good transmission and rejection characteristics in the passband and stopband, respectively. The SC-EBG band stop filter gives a 10-dB bandwidth of 3.57 GHz and ripple content of 1.85 dB in lower passband and 2.12 dB in upper passband. The SACK-EBG bandstop filter gives an improved 10-dB bandwidth of 5.25 Ghz with ripple content of 0.74 dB in lower passband and 4.8 dB in the upper pass band. The proposed SA-EBG and SACK-EBG filters give ultrawide stopband and lower ripple content in lower pass band with small circuit area. The measured and simulated results are found to be in good agreement. The Computer Simulation Technology (CST)-2010 studio suite software is used to design the filter structure and the simulated filter structure has been fabricated using Printed Circuit Board (PCB) technology and in order to have more precise practical results this fabricated design is tested on Agilent Vector Network Analyzer (VNA) with frequency range 0 -11 GHz and 4 -16 GHz.
M.E. (ECED)
Keywords: EBG; DGS; MPA